Colorectal Polyps: A Histopathological Study in Tertiary Care Center - Basnet, Dipika; Makaju, Ramesh; Gurung, Ram Bahadur; Dhakal, Rachana (Nepalese Medical Journal, 2021)
Introduction: Gastrointestinal polyps are commonly encountered in the colorectal region. They can be non-neoplastic or neoplastic. Neoplastic polyps include adenomas which are clinically important because of their premalignant nature. The study was carried out to analyze the histomorphological spectrum of polyps; in our institution with special emphasis on adenomatous polyps. Material and methods: This is a retrospective study done from January 2015 to December 2019 in the Department of Pathology, Dhulikhel Hospital - Kathmandu University Hospital (DH - KUH). Relevant clinical data of the patients were obtained from the histopathological records of the patient from the pathology department and biopsies stained with Haematoxylin and Eosin were studied under the light microscope. Results: A total of 168 cases of polyp were studied from 125 patients. The most common indication for colonoscopy in patients with polyp was per rectal bleeding. The age of the patient ranged from 2 to 83 years. The rectum was the commonest location. 106(63.1%) of polyps were non-neoplastic and 6(36.9%) of polyps were neoplastic. Juvenile polyp(71;42.3%) was the commonest polyp. Tubular adenoma(55;32.7%) was the commonest neoplastic polyp. The maximum number of neoplastic polyps were seen in the age group of 51-60years (11;29.7%). Male predominance was seen in neoplastic as well as a non-neoplastic polyp. High grade adenoma(4;6.7%) was more commonly seen in adenomatous polyp >2cm(3;75%) followed by 1-2cm(1;25%) and none in <1cm. Conclusions: This study gives a fair insight into the distribution of neoplastic and nonneoplastic polyp in the colorectal region. Adenomatous polyps are premalignant.